Software modernization by recovering Web services from legacy databases. Issue 5 (28th March 2012) - Pérez‐Castillo, Ricardo; García‐Rodríguez de Guzmán, Ignacio; Caballero, Ismael; Piattini, Mario
ABSTRACT Databases are considered to be a valuable asset for organizations because they contain all those organizations' persistent pieces of data. Both databases and the information systems that use them undergo erosion as a consequence of uncontrolled maintenance over time. However, when information systems evolve to become modernized versions of them, existing databases must not be discarded because they contain much valuable business knowledge that is not present anywhere else. Some of the software industry's current demands, such as time‐to‐market developments and the provision of software as services entail additional challenges in the reuse of legacy systems during software modernization. This paper addresses this problem and proposes a reengineering process that follows model‐driven development principles to recover Web services from legacy databases. The Web services that are mined manage access to legacy databases without discarding them. Legacy databases can thus be used by modernized information systems in service‐oriented environments. The adoption of this process is facilitated by the implementation of a support tool, which is used to conduct an industrial case study involving a real‐life legacy database. The study demonstrates that the proposal reduces development efforts and improves the return of investment by extending the lifespan of legacy databases. Copyright © 2012 John Wiley & Sons, Ltd.